1989
DOI: 10.1007/bf01871274
|View full text |Cite
|
Sign up to set email alerts
|

H+/Ca2+ exchange in rabbit renal cortical endosomes

Abstract: We have examined the effect of second messengers on ATP-driven H+ transport in an H+ ATPase-bearing endosomal fraction isolated from rabbit renal cortex. cAMP (0.1 mM) had no effect on H+ transport. Acridine orange fluorescence in the presence of 0.5 mM Ca2+ (+1 mM EGTA) was 19 +/- 6% of control. Inhibition of ATP-driven H+ transport by Ca2+ was concentration dependent; 0.25 and 0.5 mM Ca2+ (+1 mM EGTA) inhibited acridine orange fluorescence by approximately 50 and approximately 80%, respectively. Ca2+ also pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
1
8
1
1
Order By: Relevance
“…Stimulation of 45Ca 2+ uptake by the vesicles was possible, as ATP did stimulate this uptake in the present studies and in previous observations from our laboratory (Fig. 4 ofHilden & Madias, 1989). Like the response in endosomes, PCMB had no effect on 45Ca2+ uptake by BBMV (Fig.…”
Section: T)contrasting
confidence: 34%
See 1 more Smart Citation
“…Stimulation of 45Ca 2+ uptake by the vesicles was possible, as ATP did stimulate this uptake in the present studies and in previous observations from our laboratory (Fig. 4 ofHilden & Madias, 1989). Like the response in endosomes, PCMB had no effect on 45Ca2+ uptake by BBMV (Fig.…”
Section: T)contrasting
confidence: 34%
“…The mechanisms mediating the regulation of vacuolar pH are under active investigation. In recent studies, we have described the presence of a C1 conductance (Hilden, Johns & Madias, 1988), an H+/Ca 2+ exchanger (Hilden & Madias, 1989) and a Na+/H + exchanger (Hilden, Ghoshroy & Madias, 1990) in an H + ATPase-bearing endosomal fraction isolated from rabbit renal cortex. We have suggested that these secondary transporters might represent important modulators of the vacuolar H + ATPase activity.…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, after 20 min of endocytosis by cultured fibroblasts in an incubation medium containing 2 mM Ca 2ϩ , the endosomal free Ca 2ϩ concentration was estimated at ‫3ف‬ M (Gerasimenko et al, 1998). There is also evidence that lysosomes contain a mobilizable pool of Ca 2ϩ (Haller et al, 1996), and that both endosomal (Hilden and Madias, 1989) and lysosomal (Lemons and Thoene, 1991) membranes contain Ca 2ϩ transport systems. Furthermore, a rise in cytosolic Ca 2ϩ has been shown to be necessary for lysosome-lysosome fusion (Bakker et al, 1997), lysosome-phagosome fusion (Jaconi et al, 1990), and lysosome-plasma membrane fusion (Rodriguez et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Pryor et al (41) recently proposed that endocytosed Ca 2ϩ released from the lumen of endocytic organelles (such as late endosomes and lysosomes) may be used to mediate membrane fusion events at several stages of the endocytic pathway. There is also evidence demonstrating that lysosomes contain a mobilizable pool of Ca 2ϩ (44) and that endosomal (45) and lysosomal (46) membranes contain Ca 2ϩ transport systems. Furthermore, Malik et al (24) recently showed that Ca 2ϩ ionophore stimulation of M. tuberculosisinfected human macrophages leads to the demise of the intracellular mycobacteria coincidental with the progression of the bacteria to an intracellular compartment that was lysosomal and acidified.…”
Section: Discussionmentioning
confidence: 99%